2021
DOI: 10.2144/fsoa-2021-0097
|View full text |Cite
|
Sign up to set email alerts
|

Nanotopography in Directing Osteogenic Differentiation of Mesenchymal Stem Cells: Potency and Future Perspective

Abstract: Severe bone injuries can result in disabilities and thus affect a person's quality of life. Mesenchymal stem cells (MSCs) can be an alternative for bone healing by growing them on nanopatterned substrates that provide mechanical signals for differentiation. This review aims to highlight the role of nanopatterns in directing or inducing MSC osteogenic differentiation, especially in bone tissue engineering. Nanopatterns can upregulate the expression of osteogenic markers, which indicates a faster differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…Multiple studies have shown that NPs and other particulate materials are able to stimulate osteogenic differentiation of MSCs, inhibit adipogenesis, and are likely not to affect chondrogenesis [4][5][6][7][8][9]. The mechanisms of these effects are modernly obscure, while their better understanding may help to improve chondrocyte and osteocyte generation for clinical applications [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown that NPs and other particulate materials are able to stimulate osteogenic differentiation of MSCs, inhibit adipogenesis, and are likely not to affect chondrogenesis [4][5][6][7][8][9]. The mechanisms of these effects are modernly obscure, while their better understanding may help to improve chondrocyte and osteocyte generation for clinical applications [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…To visualize NPs inside the cells, MSCs were loaded with 25 µg/mL NPs for 24, fixed with 4% PFA, and analyzed by the SPNT method as described [36] using a Reichert-Jung Ultracut E ultramicrotome (Leica Microsystems GmbH, Vienna, Austria) adapted for the use of a specially designed SPM head.…”
Section: Scanning Probe Nanotomography (Spnt)mentioning
confidence: 99%
“…As highlighted with these examples, micro- and nanopatterns hold tremendous potential to influence SCs cell lineage decisions through biophysical signals. Nonetheless, they also display important limitations including difficult fabrication procedures which are furthermore associated with high costs . Many aspects need also to be considered such as pattern design, available technology, the choice of material, and the production costs .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, they also display important limitations including difficult fabrication procedures which are furthermore associated with high costs. 48 Many aspects need also to be considered such as pattern design, available technology, the choice of material, and the production costs. 48 Additionally, these structures are clearly a highly simplified representation of the topographies that exist within the different tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Osteogenic rough surfaces also increase the expression of Wnt5a together with the expression of the integrins in MSC ( Olivares-Navarrete et al, 2011 ). Importantly, the exogenous addition of Wnt5a and Wnt5a knock-down experiments demonstrated that the integrin upregulation was Wnt-dependent ( Olivares-Navarrete et al, 2011 ), suggesting a mutually reinforcing crosstalk between integrin adhesions and Wnt signalling ( Barlian and Vanya, 2022 ). Integrin regulates differentiation through the Wnt pathway, and Wnt increases the expression of integrin, resulting in further regulation of osteogenic differentiation ( Sun et al, 2018 ; Rougerie et al, 2021 ).…”
Section: Signaling Pathways Of Interface Morphology On Osteogenesismentioning
confidence: 99%